Dilema Auditor: Faktor Internal dan Eksternal Independensi - Sari, Martdian Ratna; Zuhri, Alhamdi; Natalia Wijaya, Paulina Millennia (Research Center and Case Clearing House PPM School of Management, 2021)
The need for financial information is an important component of economic development. The auditor is the party that guarantees that the financial statements are maintained credibility. However, many cases show the misuse of financial statements. This study aims to determine the effect of internal and external factors on auditor independence. This study used a Purposive Sampling as the sampling method, which is by taking a sample from the population-based on certain criteria (Sugiyono, 2013). This study used a sample of the auditor who has experience working in the KAP for at least 1 year. The type of data used is primary data in the form of a questionnaire. This study proves that the length of the auditor's relationship influences auditor independence. While this study does not prove that the provision of non-audit services, Competition among KAP, Large size of KAP, Audit period, and Relativism influence the independence of auditors.